Factors affecting the performance of pineapple smallholders in Kampung Meranek / Abdul Rahman Saili ... [et al.] - Saili, Abdul Rahman; Mohamadin, Mohammad Isa; Kamil, Mohammad Zulfikar (2005)
Samarahan has been identified as a high potential area for pineapple plantation. IADP had identified Kampung Meranek as one of the districts for pineapple production. Even with continuous help and advice since 1986, the number of successful pineapple farmers is still very low that is, one out of twenty pineapple farmers (based on IADP scheme participants). The aim of this research is therefore to identify the factors that affect the performance of smallholding pineapple farmers in Kampung Meranek.In achieving the aim, a number of objectives have been established, as outlined in Chapter One. A review of relevant literature is provided in Chapter Two, but the main emphasis of the study is concerned with empirical research, with the methods of study discussed in Chapter Three. Briefly this comprises of questionnaire survey and interviews with smallholding farmers and agriculture officers.